EXPLORING LOCAL MYTHOLOGY: FOLKLORE NAMING OF TOURIST ATTRACTIONS IN BANGKA THROUGH NARRATIVE STRUCTURE - Afandi, Rizky Arif; Ferianda, Sandy; Febiola, Tsasa Vina; Susanti, Tia Ayu (SIGEH ELT : Journal of Literature and Linguistics, 2026)
Although several tourist destinations in the Bangka Belitung Islands, particularly in West Bangka, Central Bangka, and South Bangka, derive their names from local folklore such as Mercusuar Mentok, Batu Balai, Pantai Tanjung Ular, Pantai Tapak Antu, Pantai Lampu, and Pantai Batu Berakit the narrative structures and cultural meanings embedded in these place names have received limited scholarly attention. As a result, the role of folklore-based place naming in shaping spatial identity and cultural memory within tourism contexts remains insufficiently examined.This research aims to analyze the narrative structure and cultural significance of the names of these tourist destinations using Vladimir Propp's narrative theory and Edward Said's postcolonial perspective. It employs a descriptive-interpretive qualitative approach involving field observations and semi-structured interviews with twelve local communities. Data were collected from oral narratives, literature reviews, and local documents. The findings reveal that each place name exhibits distinct narrative function patterns, including interdiction, violation, recognition, return, absentation, villainy, struggle, testing, and reward, which together shape the moral and spiritual values of the Bangka Belitung community. Additionally, the study incorporates a postcolonial view that highlights the folklorization process of these tourist attraction names in Bangka, as an effort to negotiate local identity and transform colonial influences into autonomous cultural symbols. This study contributes to the field of cultural toponymy and tourism studies by demonstrating that the naming of tourist attractions in Bangka Belitung functions not only as a geographic identifier but also as a narrative structure that preserves collective memory and operates as a postcolonial strategy of symbolic resistance, reinforcing the cultural identity of the Bangka Belitung people.Keywords: Bangka Belitung; folklore; narrative structure; postcolonial; Vladimir Propp